Teología política de Juliano como expresión de la controversia paganismo-cristianismo en el siglo IV - Hidalgo de la Vega, M. J. (Antigüedad y Cristianismo, 1990)
This study is an endeavour to analyse and explain the political theology of Julian based on the specific and detailed study of his most representative speeches on this subject. At the same time it becomes evident that the political theology adquires the form of expression of the ideological-religious fights in the pagan-Christian disputes which developed in the fourth century A.D.